Konfigurasi Filter Data ADS-B Pada ATC System Untuk Mengatasi Kestabilan dan Stuck Altitude Air Traffic Surveillance Target - dian anggraini (Langit Biru: Jurnal Ilmiah Aviasi, 2022)
Air traffic services require the precision and accuracy of the position and altitude of the aircraft. The ATC System as an important piece of equipment in air traffic services has input data from Surveillance, namely Radar and ADS-B, in the operation of the ATC System there are problems with unstable targets and inaccurate aircraft altitudes. This study aims to overcome target problems by configuring filters on ADS-B data using the action research method. The results show that setting the altitude on the filter at 200ft can reduce target problems in ATC systems that have surveillance data input from radar and ADS-B.